Synthesis and Redox Behavior of a Sheathed Cross-Conjugated Polythiophene - Sugiyasu, Kazunori; Inoue, Ryota; Shomura, Ryo; Matsushita, Yoshitaka; Takeuchi, Masayuki (Synlett, 2018)
Control over the electronic structure in π-conjugated polymers is of great importance for the development of organic electronics and spintronics. In this study, we synthesized a sheathed cross-conjugated polythiophene through oxidative electrochemical polymerization. Spectroelectrochemistry has revealed that unlike linearly conjugated polythiophenes, polarons were confined in the repeating units that were segmented by cross-conjugation.
Keywords: cross-conjugation; polythiophenes; insulated molecular wires